2017
DOI: 10.1093/ntr/ntx202
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Self-Reported Smokefree Workplace Policy Coverage Among Employed Adults—United States, 2003 and 2010–2011

Abstract: Introduction The workplace is a major source of exposure to secondhand smoke from combustible tobacco products. Smokefree workplace policies protect nonsmoking workers from secondhand smoke and help workers who smoke quit. This study examined changes in self-reported smokefree workplace policy coverage among U.S. workers from 2003 to 2010–2011. Methods Data came from the 2003 (n = 74,728) and 2010–2011 (n = 70,749) waves of the Tobacco Use Supplement to the Current Population Survey. Among employed adults wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Studies have found that smoke‐free policies are not equally applied in outdoor places or workplaces, which may contribute to disparities; for example, although 80% of US indoor workers were covered by a workplace smoke‐free policy, this proportion was lower among younger workers, males, Hispanics, and those with less education or income or who lived in the South . Enhancing equitable implementation of comprehensive smoke‐free strategies in all workplaces, public places, homes, and vehicles can reduce secondhand smoke exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that smoke‐free policies are not equally applied in outdoor places or workplaces, which may contribute to disparities; for example, although 80% of US indoor workers were covered by a workplace smoke‐free policy, this proportion was lower among younger workers, males, Hispanics, and those with less education or income or who lived in the South . Enhancing equitable implementation of comprehensive smoke‐free strategies in all workplaces, public places, homes, and vehicles can reduce secondhand smoke exposure.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 The number of indoor workers covered by a smoke-free policy increased from 69.3% in 1999 to 82.8% in 2010–2011; however, policy coverage varies across population groups. 12,13…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies have assessed smoke-free policies at workplaces, findings were limited to food service workers and major occupation groups. 12,13 Additionally, information on detailed industry- and occupation-specific smoke-free workplace policy and employer-sponsored cessation program coverage is limited. To fill these gaps, this study used data from the 2014–2015 Tobacco Use Supplement to the Current Population Survey (TUS-CPS) to assess the extent of combustible tobacco use, as well as coverage of smoke-free policies and employer cessation programs, among employed U.S. adults, by industry and occupation.…”
Section: Introductionmentioning
confidence: 99%
“…In other developed countries, the reported proportion of indoor workers covered by such policies has increased overall, such as among whitecollar and blue-collar workers, as well as service workers. 30 Even so, comprehensive smoke-free policies in very small workplaces are not very common 31 ; therefore, much stronger laws are needed to create working environments that are indeed smoke free.…”
Section: Influence Of Occupation On Smoking Prevalencementioning
confidence: 99%